2017
DOI: 10.1038/ncomms14706
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes promote malignant growth of breast tumours with monocarboxylate transporter 2 expression via β-hydroxybutyrate

Abstract: Adipocytes are the most abundant stromal partners in breast tissue. However, the crosstalk between breast cancer cells and adipocytes has been given less attention compared to cancer-associated fibroblasts. Here we find, through systematic screening, that primary mammary gland-derived adipocytes (MGDAs) promote growth of breast cancer cells that express monocarboxylate transporter 2 (MCT2) both in vitro and in vivo. We show that β-hydroxybutyrate is secreted by MGDAs and is required to enhance breast cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 49 publications
5
82
0
1
Order By: Relevance
“…Similar findings with metabolic coupling between stromal and cancer cells involving lactate, pyruvate, beta-hydroxybutyrate, acetate, fatty acids, glutamine and alanine have been discovered in many human malignancies including breast, ovarian, prostate, liver, colon, pancreatic and head and neck squamous cell cancer (HNSCC) [23] [29] [36] [37] [38] [39] [40] [41] [42] [43] [44] [45] [46] [47]. …”
Section: Monocarboxylate Transporterssupporting
confidence: 61%
“…Similar findings with metabolic coupling between stromal and cancer cells involving lactate, pyruvate, beta-hydroxybutyrate, acetate, fatty acids, glutamine and alanine have been discovered in many human malignancies including breast, ovarian, prostate, liver, colon, pancreatic and head and neck squamous cell cancer (HNSCC) [23] [29] [36] [37] [38] [39] [40] [41] [42] [43] [44] [45] [46] [47]. …”
Section: Monocarboxylate Transporterssupporting
confidence: 61%
“…Thus, studies investigating proteomic and phenotypic changes in breast cancer cells are clinically important. Previously, the differential regulation of rationally targeted proteins has been investigated following co-culture with CAA (14,17,18). In this study, we identified global protein abundance and associated pathways that are differentially regulated in two well-characterised breast cancer cell lines, representing key breast cancer molecular subtypes (hormone receptor positive, MCF7; triple negative, MDA-MB-231), following 3-day transwell co-culture with human breast adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies, using transwell (non-contact) co-culture of mature adipocytes with breast cancer cells, have established that CAA promote breast cancer cell proliferation, viability, migration and invasion (2, 8, [13][14][15][16][17][18]. Recent evidence suggests that cross talk with CAA induces breast cancer cell invasiveness, in part, through metabolic remodelling of the cancer cell, promoting a shift towards increased mitochondrial fatty acid oxidation (17,19).…”
mentioning
confidence: 99%
“…Importantly, the coexistence of adipocytes and tumor cells potentiates both ketogenesis in adipocytes as well as ketolytic activity in BC cells [142]. Additionally, it was shown that β-hydroxybutyrate secreted from adipocytes enhanced BC cells malignancy in vitro, upregulating several tumor-promoting genes in BC cells [144]. Induction of ketone-specific gene signature was shown to be associated with worse outcomes in BC patients [145].…”
Section: Metabolic Shiftmentioning
confidence: 99%